Effect of potassium fulvate on continuous tobacco cropping soils and crop growth - Jiao, Yingle; Chen, Qian; Guo, Xiaomeng; Li, Hongliang; Chen, Xuwei; Men, Kuifu; Liu, Xiaochen; Shang, Xianchao; Gao, Yun; Zhang, Li; Yang, Long; Hou, Xin (Frontiers in Plant Science, 2024)
Long-term continuous cropping of tobacco causes dysbiosis of soil microbial communities, the imbalance of soil nutrients, and the increase of pathogenic bacteria, which will slow the growth and development of tobacco plants, reduce the production quality, and cause significant losses to tobacco production and tobacco farmers. The application of Potassium fulvic acid can not only provide nutrients, but also inhibit the propagation of pathogens in soil along with raising the amount of organic matter in the soil, which is an effective way to improve soil health. In this experiment, Tobacco variety SNT60 was used as the test material, and 6 treatments were set up by pot test, they were: no fertilization control group (CK), tobacco special fertilizer (NPK), 3.45 g/kg of potassium fulvic acid fertilizer (T1), 4.65 g/kg of potassium fulvic acid fertilizer (T2), 5.85 g/kg of potassium fulvic acid fertilizer (T3), 7.05 g/kg of potassium fulvic acid fertilizer(T4), Ten replications were set up for each treatment and the soil and fertiliser were mixed and potted before transplanting, 70% as basal fertiliser and 30% as supplementary fertiliser. We also analyzed soil properties, soil microorganisms and agronomic traits of tobacco plants in different treatments to provide reference for mitigating tobacco succession barrier. The test results are as follows: 4.65 g/kg of potassium fulvic acid fertilizer (T2) treatment was the best, soil organic matter, quick nitrogen, phosphorus, potassium, pH, soil catalase, soil sucrase, and soil urease content, compared to CK control, increased by 22.04%, 43.12%, 96.21%, 381.79%, 25.43%, 91.69%, 262.07% and 93.16%. In terms of microbial community, application of potassium fulvic acid fertilizer significantly increased the relative abundance of Ascomycetes, Chlorobacterium, Bacillus, Proteobacteria and Tephritobacterium in the soil. Meanwhile, 4.65 g/kg of potassium fulvic acid fertilizer (T2) promoted the growth of tobacco plants, improved leaf photosynthetic capacity, and enhanced plant disease resistance. This experiment provides practical measures to improve the microbial community of tobacco continuous cropping soils and to reduce the incidence of diseases.